To determine which expression correctly uses the Product Rule of Exponents, we need to recall the Product Rule itself: \( a^m \cdot a^n = a^{m+n} \).
We are looking for an expression that, when simplified using this rule, results in \( 24^{12} \).
Let's analyze each option:
-
\( 24^4 \cdot 24^8 \):
- Using the Product Rule: \( 24^4 \cdot 24^8 = 24^{4+8} = 24^{12} \)
- This is correct.
-
\( 6^4 \cdot 4^3 \):
- This does not have the same base, so it cannot be simplified to \( 24^{12} \) using the Product Rule.
-
\( 24^3 \cdot 24^4 \):
- Using the Product Rule: \( 24^3 \cdot 24^4 = 24^{3+4} = 24^{7} \)
- This is incorrect.
-
\( 12^4 \cdot 12^8 \):
- Using the Product Rule: \( 12^4 \cdot 12^8 = 12^{4+8} = 12^{12} \)
- This does not produce \( 24^{12} \), so it is incorrect.
The only expression that simplifies correctly to \( 24^{12} \) using the Product Rule is \( 24^4 \cdot 24^8 \).